Rockaway Blue : A Novel - Kirwan, Larry (Book collections on Project MUSE., 2021)
"On 9/11 Lieutenant Brian Murphy, NYPD, ran back into the collapsing North Tower. He was off duty and had not returned home the night before. Three years later his father, retired Detective-Sergeant Jimmy Murphy, sets out to find the truth about his son, his family, and his country"--